Peran Pendidikan Kewirausahaan dalam Minat Mahasiswa Menjadi Entrepreneur - Ichwan Arifin; Zainal Arif; Sabik Khumaidi; Fathurrahman (Masyarakat Ekonomi Syariah Bogor, 2025)
In today's era, various business sectors are developing rapidly. Not only is information technology booming, but other business sectors are also expanding. One such sector is entrepreneurship. However, currently, fostering interest in entrepreneurship among the public, particularly among students, is very difficult due to a lack of knowledge and the lack of opportunities to start a business. In fact, entrepreneurship is expected to reduce current unemployment. A graduate is required to be able to create jobs, not just look for them; this will also be useful for people who need them. The government, of course, cannot fully provide jobs due to numerous obstacles, one of which is funding. Entrepreneurship can be initiated and developed by many factors, one of which is education. Through entrepreneurship education, it is hoped that it will spark interest and increase students' curiosity about entrepreneurship, thereby developing an entrepreneurial attitude that will produce new entrepreneurs. Entrepreneurship education is expected to inspire enthusiasm for entrepreneurship, creativity, and development of new things. This provides an opportunity for students to compete for capital, which can later be used as initial capital for running a business. Entrepreneurship courses play a crucial role in fostering entrepreneurial interest, which is intended to provide students with practical experience from businesses, whether large, medium, or small. By providing students with a basic understanding of entrepreneurship, they will have the opportunity to directly engage in the world of entrepreneurship. The purpose of this study is to determine the role of entrepreneurship education in student interest in becoming entrepreneurs. The research method used is qualitative, with data collection methods including questionnaires, interviews, and observations. The targeted output is the Misykat al-Anwar Journal, a journal of Islamic and Community Studies at the Faculty of Islamic Studies (FAI) of the State Islamic University of Muhammadiyah Yogyakarta (UMJ), which, God willing, will be published in November 2024.